Can clothing systems and human activity in operating rooms with mixed flow ventilation systems help achieve the ultraclean air requirement (≤10 CFU/m3) during orthopaedic surgeries?. (February 2022) - Cao, G.; Pedersen, C.; Zhang, Y.; Drangsholt, F.; Radtke, A.; Langvatn, H.; Stenstad, L-I.; Mathisen, H.M.; Skogås, J.G.
Summary: Objectives: The level of airborne microbial contamination in operating rooms (ORs) is an important indicator of indoor air quality and ensures a clean surgical environment. The main objective of this study was to clarify the possibility of achieving the requirement for an ultraclean operating room (≤ 10 CFU/m 3 ) with mixed flow ventilation based on clothing and human activity. Methods: Experimental measurements during mock surgeries were conducted in an actual OR with mixed flow ventilation in the Emergency, Heart and Lung Centre at St. Olavs Hospital in Trondheim. The bacterial concentration close to the surgical site was measured during five mock-up surgeries. All five mock-up surgeries followed real surgical procedures which could represent similar conditions in the OR. Results: The experiment results verified that the average CFU/m 3 of three of the five mock-up surgeries was 8.5, which was below or equal to the ultraclean requirement, while the other two mock-up surgeries did not meet the ultraclean requirement. Surgical activity together with the type of clothing worn by surgical staff in ORs seem to be the most significant reason for the high CFU level during surgery. Conclusions: It is possible to achieve the ultraclean air requirement (≤ 10 CFU/m 3 ) during a surgical process with proper clothing and low surgical activity in ORs. This study clarifies the effect of clothing and human activity on the CFU level in the surgical micro-environment in ORs, and contributes to developing new products for the surgical team.